Implementation of The Free Nutritious Meal (MBG) Program Policy, in North Sulawesi - Joyce Jacinta Rares; Michael Mamentu; Emma Valentina Theresia Senewe (Universitas Muhammadiyah Gorontalo, 2025)
The Free Nutritious Meal Program/Makan Bergizi Gratis (MBG) is a national priority policy under President Prabowo Subianto, aimed at addressing stunting, malnutrition, and inequality in access to healthy food. This study aims to analyze the implementation of the MBG policy in North Sulawesi Province in 2025, identify field constraints, and evaluate the effectiveness of program distribution. Theoretically, this study uses Merilee S. Grindle's policy implementation model, which emphasizes two main dimensions: policy content and implementation context. The research method used was descriptive qualitative. Data were collected through field observations at Nutrition Fulfillment Service Units (SPPG), documentation, and in-depth interviews with eight key informants, including representatives from the ministry, SPPG heads, and beneficiary school principals. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, using triangulation techniques to ensure the validity of the findings. The results indicate that the implementation of the MBG Program in North Sulawesi has not fully aligned with the policy's ideal objectives. Until 2025, the program's implementation will only reach students (kindergarten through high school), while the most vulnerable groups, such as toddlers, pregnant women, and breastfeeding mothers, have not received services. Yet, interventions during the first 1,000 days of life are crucial for significantly reducing stunting rates. Geographically, program distribution remains concentrated in urban areas with easy access, while the Disadvantaged, Frontier, and Outermost (3T) regions and island regions such as Talaud, Sangihe, and Sitaro have not been reached optimally.